THE INFLUENCE OF VARIOUS CONCENTRATED CHERRY (MUNTINGIA CALABURA) EXTRACT IN PREVENTING LACTOBACILLUS ACIDOPHILUS IN VITRO - Nurhalisa, Siti; Lestari, Endang Sri; Wibisono, Gunawan; Indraswari, Darmawati Ayu (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: Dental caries is a multifactorial illness caused by bacteria. Lactobacillus acidophilus is one of the bacteria causing caries, where it continues the caries process. That is why the antibacterial agent is needed. A cherry (Muntingia calabura) is fruit having many benefits for health, which one of them is as an antibacterial agent. It contains flavonoid, tannin, alkaloid, and terpenoid, which can function as the antibacterial agent. Aim :The study aimed to determine the influence of cherry (Muntingia Calabura) extract in preventing the growth of L.acidophilus. Method: True experimental laboratory with a post-test only control group design and 24 samples. Cherries were extracted by using maceration. Then, the phytochemical test was conducted to discover antibacterial substances. The antibacterial test was done by using the dilution method to know Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Results: Minimum Inhibitory Concentration (MIC) could not be seen, and Minimum Bactericidal Concentration (MBC) showed that all concentration 6,25%, 12,5%, 25%, and 50% and positive control were able to kill a bacterium L. acidophilus. Conclusions: There is an influence of cherry extract on the grow